The Elixir of Life: Hawthorne and Jardiel Poncela - Álvarez Castaño, Emilio (European Public & Social Innovation Review, 2025)
Introduction: This study explores the concept of the elixir of life, a mythical potion present in diverse cultures and literatures, through a comparative analysis of two works: 'Dr. Heidegger's Experiment' by Nathaniel Hawthorne and the comedy 'Cuatro corazones con freno y marcha atrás' by Enrique Jardiel Poncela. Methodology: The analysis begins with a historical review of the elixir of life to establish a common context. Both literary works are then analysed, addressing the biographical and literary contexts of Hawthorne and Jardiel Poncela that are relevant to the study. Results: Both authors' perspectives on the elixir of life are examined, noting how each integrates this fantastic element into their narrative. Hawthorne and Jardiel Poncela, coming from different cultural and temporal contexts, offer distinct approaches that reflect their respective societies and times. It highlights how the works differ in their structure, development and the implications of the use of the elixir. Conclusions: The study highlights the richness of interpretations of the myth of the elixir of life in literature, showing that, despite cultural and temporal differences, this mythical theme continues to fascinate and offer new angles of analysis on the human condition and the desire for immortality.